Exploring the Integration of Artificial Intelligence in Primary Education: A Systematic Literature Review (2020–2024) - Maharani Revenaya; Bambang Subali; Ellianawati Ellianawati (Universitas Negeri Surabaya, 2025)
Artificial intelligence (AI) is increasingly transforming primary education by enabling adaptive, personalized, and interactive learning. This study presents a systematic literature review (SLR) of 54 Scopus-indexed articles published between 2020 and 2024 to explore trends, applications, benefits, and challenges of AI integration in primary education. The review followed PRISMA 2020 guidelines and combined bibliometric and thematic analyses. Biblioshiny was applied to examine publication trends and contributing countries, while VOSviewer visualized keyword co-occurrence and thematic clusters. Results indicate steady growth in research, with China, the United States, and Europe leading contributions. Nine categories of AI applications were identified, particularly machine learning, deep learning, and natural language processing. Reported benefits include personalization, improved engagement, inclusive education support, teacher efficiency, and digital literacy development. However, significant challenges remain, such as limited infrastructure, insufficient teacher readiness, financial constraints, and concerns over children’s data privacy. The study concludes that while AI holds strong potential to enhance primary education, successful implementation depends on ecosystem readiness, equitable access, and ethical safeguards. This review contributes by mapping global research trends, consolidating fragmented evidence, and offering practical insights for educators, policymakers, and researchers.